ISLAMIC EDUCATION INTITUTIONS IN THE CLASSICAL PERIOD (UMAYYAD AND ABBASID PERIODS) - Hidayah, Nurul; Faridi, Faridi; Ishomuddin, Ishomuddin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
Islamic education has existed since the Prophet Muhammad SAW and continues to develop until now. Islam once reached the peak of glory, called the golden age, because, at that time, Islamic education was very developed and produced an extraordinary scientific civilization recognized throughout the world with evidence of the development of various Islamic educational institutions during the Classical period. Therefore, it is essential to know the history of Islamic education, especially during the classical era of the Umayyads and Abbasids, to learn from this history. The aim of this research is the institution of Islamic education during the Classical period of the Umayyads and Abbasids. The research method uses library research by collecting various sources of books, articles, and documents about Islamic educational institutions during the Umayyad and Abbasid eras. The results of the study show that Islamic Educational Institutions began to develop during the Umayyad period, such as the Kuttab, Khan, and other Madrasas, then reached their peak during the Abbasid era, such as the Kuttab, Library, and Observatory, elementary, middle to high-level Madrasas. However, not long after that, the Abbasids were destroyed, and Islamic education began to decline. Therefore, it is essential not to be lulled by progress glory days and to continue to love science so that Islamic education can develop as before.